BELAJAR SEHAT DENGAN CARA MENYENANGKAN: IMPLEMENTASI KARTU SEHAT DI SEKOLAH DASAR - Mariani Angeline; Saula Rahmadianti Krisma Pertiwi; Aurelia Naftali Kalengkongan; Bernike Burnama; Novario Jaya Perdana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
ABSTRACT Awareness of the importance of health from an early age is a fundamental aspect in shaping healthy lifestyle living behaviours among children. Monitoring student's health is essential as it directly affects the quality of education, development, and the future of the students. Good health enables children to learn more effectively, enhances concentration, and supports better academic archievement. Previous studies have shown that similar programs can increase the understanding of students, parents, and educators regarding the importance of periodic health check-ups. Therefore, this activity aims to help students understand the signifivance of maintaining their health from an early age, which is crucial in establishing a sustainable healty lifestyle. This study aims to improve elementary school student's health awareness through the use of a